Hubungan Antara Keterampilan Proses Sains Terintegrasi dan Efikasi Diri dengan Literasi Biologi Siswa - Ratna Dewi Wulaningsih; Nurmasari Sartono; Sarah Rahmawati Nurmanita (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2022)
The rapid development of science and technology in the era of globalization requires educational institutions to be able to form students who have scientific literacy skills. Biology is a branch of science. Biological literacy is the development of scientific literacy in a biological context. Science problems, especially biology, that exist in everyday life can be solved if students understand and can use integrated science process skills and high self-efficacy. It is intended that every decision taken when solving problems has a strong foundation and students will be able to develop in achieving achievements and feel optimistic in achieving something. This study aims to determine the relationship between integrated science process skills and self-efficacy with students' biological literacy. This research was conducted at SMA Negeri 3 Depok in the odd semester 2021/2022 academic year. The method used is descriptive method, with the type of correlational study. The sample used was 144 students taken from four classes of X Mathematics and Natural Sciences using simple random sampling technique. The data in this study were taken using three test instruments, namely: a biological literacy test, an integrated science process skills test and a self-efficacy test. The results showed that there was a positive relationship between integrated science process skills and biological literacy, a positive relationship between self-efficacy and biological literacy, a positive relationship between integrated science process skills and students' self-efficacy and biological literacy.Â Keywords: self-Efficacy, integrated science process skills, biological literacy